Diabetes and altered glucose metabolism with aging - Kalyani, Rita Rastogi; Egan, Josephine M (Endocrinology and metabolism clinics of North America, 2013)
Diabetes and impaired glucose tolerance affect a substantial proportion of older adults. Abnormal glucose metabolism is not a necessary component of aging. Older adults with diabetes and altered glucose status likely represent a subset of the population at high risk for complications and adverse geriatric syndromes. Goals for treatment of diabetes in the elderly include control of hyperglycemia, prevention and treatment of diabetic complications, avoidance of hypoglycemia, and preservation of quality of life. Research exploring associations of dysglycemia and insulin resistance with the development of adverse outcomes in the elderly may ultimately inform use of future glucose-lowering therapies in this population.